Global Financial Stability Report, April 2011 : Durable Financial Stability: Getting There from Here. (Global Financial Stability Report; Global Financial Stability Report ;, 2011)
Despite ongoing economic recovery and improvements in global financial stability, structural weaknesses and vulnerabilities remain in some important financial systems. The April 2011 Global Financial Stability Report highlights how risks have changed over the past six months, traces the sources and channels of financial distress with an emphasis on sovereign risk, notes the pressures arising from capital inflows in emerging economies, and discusses policy proposals under consideration to mend the global financial system.